Socialism equals death, market equals life: anti-socialist and pro-market policy discourse among the contemporary Venezuelan Opposition. - Barry Cannon (Les Cahiers de Framespa)
While there has been much coverage in the media and in academic work on the crisis in Venezuela, little has been written about the Venezuelan Opposition, grouped in the Democratic Unity Coalition (MUD) and even less about their economic and social policies. This paper seeks to address this latter lacuna by providing a critical examination of three key MUD policy documents. Situating this analysis within a wider discussion on the relationship between democracy and neoliberalism, and using a framework derived from Wendy Brown’s book “In the Ruins of Neoliberalism”, the article argues that the Venezuelan Opposition is fundamentally neoliberal in ideological orientation. This means that it seeks to, paraphrasing Brown, critique and dismantle society, using anti-socialism as its principle trope to do so; attack “democracy understood as popular sovereignty and shared political power”, even while it uses democracy as its main discursive banner; and extend the personal protected sphere at the expense of the public. This may result, the article concludes, in a form of neoliberal authoritarianism rather than ‘restored’ democracy as the Opposition claims.